Intravenous aflibercept in patients with platinum‐resistant, advanced ovarian cancer: Results of a randomized, double‐blind, phase 2, parallel‐arm study. Issue 3 (11th October 2013) - Tew, William P.; Colombo, Nicoletta; Ray‐Coquard, Isabelle; del Campo, Josep M.; Oza, Amit; Pereira, Deolinda; Mammoliti, Serafina; Matei, Daniela; Scambia, Giovanni; Tonkin, Katia; Shun, Zhenming; Sternas, Lars; et al.
Abstract : BACKGROUND: In this randomized phase 2 study, the authors assessed the efficacy and safety of intravenous aflibercept at 2 different doses (2 mg/kg or 4 mg/kg) in patients with recurrent, platinum‐resistant ovarian, peritoneal, or fallopian tube cancer who developed disease progression after receiving topotecan and/or pegylated liposomal doxorubicin. METHODS: Patients were randomized to receive intravenous aflibercept at a dose of either 2 mg/kg or 4 mg/kg every 2 weeks until they developed disease progression or significant toxicity. The primary endpoint was to evaluate Response Evaluation Criteria in Solid Tumor response rates (overall response rate [ORR] = complete responses plus partial responses) and to test the null hypothesis (ORR, >5%). Secondary endpoints included time to tumor progression, safety, progression‐free survival/overall survival, drug pharmacokinetics, and immunogenicity. In total, 67 evaluable patients per cohort were planned based on a Simon 2‐stage design, and, if those patients responded, then enrollment could extend to 200 patients. Tumor radiographic response was assessed by investigators and by an independent review committee. RESULTS: After the first 84 evaluable patients, 8 unconfirmed partial responders were noted (ORR, 10%) across both arms; the Independent Data Monitoring Committee recommended continuing blinded accrual. At study completion, 215 evaluable patients were accrued, including 1 responder of 106 patients (0.9%) in the 2‐mg/kg cohort and 5 responders of 109 patients (4.6%) in the 4‐mg/kg cohort according to the independent review committee. The clinical benefit rate (ORR plus stable disease >6 months) was 12.3% and 11% in the 2‐mg/kg and 4‐mg/kg cohorts, respectively. Treatment‐related grade 3 and 4 adverse events included hypertension (25.5% and 27.5% in the 2‐mg/kg and 4‐mg/kg cohorts, respectively), proteinuria (9.4% and 7.3%, respectively), and fatigue (5.7% and 3.7%, respectively). The gastrointestinal perforation rate was low (3 patients; 1.4%). CONCLUSIONS: Aflibercept at a dose of either 2 mg/kg or 4 mg/kg was generally well tolerated but did not meet the primary endpoint for response. Cancer 2014;120:335–343 . © 2013 American Cancer Society . Abstract : Intravenous aflibercept at doses of 2 mg/kg and 4 mg/kg is generally well tolerated but does not have significant activity to recommend further investigation in women with platinum‐resistant, heavily pretreated ovarian cancer. Future studies could be considered in combination with chemotherapy.